Guilt and/or self-esteem as consequences of religion - Belgum, David Rudolph (Journal of religion and health, 1992)
Our discussion begins with a consideration of the various types of religion and of guilt. Both religion and morality function in different ways from individual to individual. All these factors need to be taken into account before we can turn to treatment for the painful experience of guilt and bring about an improved self-esteem.